Model Pembelajaran Passing Futsal Menggunakan Cooperative Learning Tipe Teams Games Tournaments Untuk Siswa Sekolah Menengah Pertama - Firnando Putra Alamsyah; Eko Prabowo; Kurnia Tahki (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
This thesis describes the futsal passing learning model using cooperative learning type teams games tournaments for junior high school students. This research method uses Research and Development (R&D) research using ADDIE theory. In this study, 14 learning models have been created that have gone through validation tests from three experts from the field of learning experts, futsal experts and physical education teachers. The 14 learning models are divided into three parts, which consist of learning to pass using the inside, outside, instep foot. The results of this study are intended as a reference material for teachers in providing more models and methods that can be used in learning to improve learning outcomes and basic futsal passing technique skills for students. And as a reference for students who will later write a thesis with similar material. Keywords: Learning Model, Passing, Futsal, Teams Games Tournaments.